Challenges and opportunities in the early diagnosis and optimal management of rheumatoid arthritis in Africa and the Middle East. (13th March 2014) - Halabi, Hussein; Alarfaj, Abdurhman; Alawneh, Khaldoon; Alballa, Soliman; Alsaeid, Khalid; Badsha, Humeira; Benitha, Romela; Bouajina, Elyes; Al Emadi, Samar; El Garf, Ayman; El Hadidi, Khaled; Laatar, Ahmed; et al.
Abstract Early diagnosis and early initiation of disease‐modifying antirheumatic drug (DMARD) therapy slow the progression of joint damage and decrease the morbidity and mortality associated with rheumatoid arthritis (RA). According to the European League Against Rheumatism (EULAR) guidelines, treatment should be initiated with methotrexate and addition of biological DMARDs such as tumour necrosis factor (TNF) inhibitors should be considered for RA patients who respond insufficiently to methotrexate and/or other synthetic DMARDs and have poor prognostic factors. Africa and the Middle East is a large geographical region with varying treatment practices and standards of care in RA. Existing data show that patients with RA in the region are often diagnosed late, present with active disease and often do not receive DMARDs early in the course of the disease. In this review, we discuss the value of early diagnosis and remission‐targeted treatment for limiting joint damage and improving disease outcomes in RA, and the challenges in adopting these strategies in Africa and the Middle East. In addition, we propose an action plan to improve the overall long‐term outlook for RA patients in the region.